Strategic Leadership in the Digital Age to Strengthen Digital Citizenship in Educational Institutions - Ruli Astuti; Slamet Slamet; Khizanatul Hikmah (Academia Open, 2025)
General Background: Digital citizenship—encompassing safe, responsible technology use, critical media literacy, and ethical engagement—is increasingly vital in today’s educational landscape. Specific Background: Strategic leadership, defined by vision, innovation, and adaptability, plays a pivotal role in guiding schools through digital transformation. Knowledge Gap: However, existing scholarship has yet to integrate leadership practices with a coherent framework for cultivating digital citizenship in K–12 settings. Aims: This study employs a literature review to synthesize relevant research and construct a comprehensive model linking strategic leadership behaviors to digital competency development. Results: Analysis reveals that effective leaders articulate long-term digital visions, align institutional strategies with technological goals, foster collaborative innovation, and model ethical online conduct, thereby facilitating responsible student engagement. Novelty: The resulting framework uniquely maps leadership dimensions—visioning, strategy alignment, culture building—to specific digital citizenship outcomes. Implications: Policymakers and practitioners can leverage these insights to design leadership development programs and institutional policies that empower students as competent, ethical digital citizens in the twenty-first-century learning environment. Highlights: Vision-driven strategy propels digital goals Institutional alignment ensures coherent tech integration Ethical culture underpins responsible online behavior Keywords: Strategic Leadership, Technology Integration, Digital Citizenship, Ethical Digital Behavior